Cutaneous exposure to clinically-relevant pigeon pea (Cajanus cajan) proteins promote TH2-dependent sensitization and IgE-mediated anaphylaxis in Balb/c mice. (1st November 2016) - Kumar Gupta, Rinkesh; Kumar, Sandeep; Gupta, Kriti; Sharma, Akanksha; Roy, Ruchi; Kumar Verma, Alok; Chaudhari, Bhushan P.; Das, Mukul; Ahmad Ansari, Irfan; Dwivedi, Premendra D.
Abstract: Epicutaneous (EC) sensitization to food allergens may occur when the skin has been lightly damaged. The study here tested whether cutaneous exposure to pigeon pea protein(s) may cause allergic sensitization. BALB/c mice were either orally gavaged or epicutaneously sensitized by repeated application of pigeon pea crude protein extract (CPE) on undamaged areas of skin without any adjuvant; afterwards, both groups were orally challenged with the pigeon pea CPE. Anaphylactic symptoms along with measures of body temperature, MCPT-1, TSLP, pigeon pea-specific IgE and IgG1, myeloperoxidase (MPO) activity, TH 2 cytokines, TH 2 transcription factors (TFs) and filaggrin expression were determined. Mast cell staining, eosinophil levels and histopathological analysis of the skin and intestines were also performed. In the epicutaneously-sensitized mice, elevated levels of specific IgE and IgG1, as well as of MCPT-1, TSLP, TH 2 cytokines and TFs, higher anaphylactic scores and histological changes in the skin and intestine were indicative of sensitization ability via both routes in the pigeon pea CPE-treated hosts. Elevated levels of mast cells were observed in both the skin and intestine; increased levels of eosinophils and MPO activity were noted only in the skin. Decreased levels of filaggrin in skin may have played a key role in the skin barrier dysfunction, increasing the chances of sensitization. Therefore, the experimental data support the hypothesis that in addition to oral exposure, skin exposure to food allergens can promote TH 2-dependent sensitization, IgE-mediated anaphylaxis and intestinal changes after oral challenge. Based on this, an avoidance of cutaneous exposures to allergens might prevent development of food anaphylaxis.